2005
DOI: 10.1021/ef049850g
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of the Effects of Water Addition on the Exhaust Emissions of a Naturally Aspirated, Liquefied-Petroleum-Gas-Fueled Engine

Abstract: The purpose of this study is to evaluate the effect of water addition on combustion in a conventional SI engine. The manifold induction method is used for water addition in this study. The exhaust emissions, ignition timing, and exhaust temperature values were measured for different equivalence ratio values by using a naturally aspirated liquefied-petroleum-gas-fueled spark ignition, four-cylinder engine. The water induction is accomplished over a wide range of water to fuel mass ratios of 0.2−0.5. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The high heat of vaporization of water will decrease temperature and reduce fuel-air mixture. The long burning period, low fuel-air mixture temperature would contribute to higher HC emission (Özcan and Söylemez, 2005). The HC emission factors of P5B15W1 increased by 12-23% and 6-11% at various loads to the P5B15 and P5B15W05, respectively.…”
Section: Unburned Hydrocarbon Emissionsmentioning
confidence: 99%
“…The high heat of vaporization of water will decrease temperature and reduce fuel-air mixture. The long burning period, low fuel-air mixture temperature would contribute to higher HC emission (Özcan and Söylemez, 2005). The HC emission factors of P5B15W1 increased by 12-23% and 6-11% at various loads to the P5B15 and P5B15W05, respectively.…”
Section: Unburned Hydrocarbon Emissionsmentioning
confidence: 99%
“…For an emulsion containing 15% of water, the authors showed a decrease of 30% in NOx and 60% in particle emissions; however, the CO and HC emissions increased. Other types of fuel have also been studied such as LPG [14] and recently pure hydrogen [15].…”
Section: Introductionmentioning
confidence: 99%
“…For a typical automotive absorption cooling system sizing problem, heat exchanger cost data [11], vapor compression air-conditioning unit cost data [11], absorption air-conditioning unit cost data [11], and a sample test engine performance data [12] are available as, m ¼ 0:028 kg s…”
Section: Resultsmentioning
confidence: 99%
“…The optimum net savings is about 1256$ and the value of payback is determined as 4.6 years by means of Equation (13) for this sample problem. The optimum exhaust gas outlet temperature is calculated as 2258C lower than the exhaust gas inlet temperature by using Equation (12) for the optimum system size. On the other hand, the critical effectiveness value is found approximately to be 0.98 by using Equation (15).…”
Section: Resultsmentioning
confidence: 99%